Influence of Thermophysical Features on MHD Squeezed Flow of ‎Dissipative Casson Fluid with Chemical and Radiative Effects - Mojeed Akolade; Taofeeq Adeosun; John Olabode (Journal of Applied and Computational Mechanics, 2021)
Theoretical investigation of variable mass diffusivity, thermal conductivity, and viscosity on unsteady squeezed flow of dissipative Casson fluid is presented. Physically, for any effective heat and mass transfer process, a proper account of thermophysical properties in such a system is required to attain the desired production output. The magnetized free convective flow of unsteady Casson fluid encompassing Joule dissipation, radiation, and chemical reactive influence is induced as a result of squeezing property. The governing model assisting the magnetized flow is formulated and transformed via an appropriate similarity transformation. The resulting set of ordinary differential equations is solved numerically using Chebyshev based Collocation Approach (CCA). However, variable viscosity, thermal conductivity, and mass diffusivity effects are seen to diminish the fluid flow velocities, temperature, and concentration respectively along with the lower plate. Heat and mass transfer coefficient, skin friction downsized to an increasing value of variable thermal and mass diffusivity parameters while variable viscosity pronounces the skin friction coefficient. Furthermore, the present analysis is applicable in polymer processing, such as injection molding, extrusion, thermoforming among others.